Exploring the Factors Influencing the Selection of Traditional Travel Agencies: A Case of Banjarmasin, Indonesia - Jeetesh Kumar; V. S. S. Shreya; Rupam Konar (Centre For Tourism Planning and Development, 2021)
Highly developed online facilities by travel agents have grown drastically over the past years. Internet is taking over the businesses of traditional travel agents in their existing as well as emerging markets. Due to the dynamic and diverse nature of technology, the travellers are seeking to optimize their travel attitude in an effective manner while implicating several threats. Amidst all changes, this study investigated the attitude of Indonesian travellers visiting traditional travel agents. A self-administrated online survey was used to collect the data from local travellers of Banjarmasin, Indonesia. A sample of 277 respondents showed a significant relationship between the expertise of travel agents, handling capacity, technological adoption towards visiting traditional travel agents. Interestingly, the social interaction factor has no significant influence. Further, the analysis identified that secure transaction shows a partial mediating effect between travellers visiting traditional travel agents and their habitual selection behaviour. The results of the study indicate that Indonesian travellers have an overall positive attitude towards traditional travel agencies due to their expertise and handling capacity of travel services. An important finding reveals transactional security as a vital factor in habitual selection behaviour of Indonesian travellers. In future, there is a necessity for a holistic approach towards the understanding of both demand and supply perspectives of travel services.